2023
DOI: 10.1021/acschemneuro.2c00772
|View full text |Cite
|
Sign up to set email alerts
|

Structure–Activity Relationship of N-Ethyl-Hexedrone Analogues: Role of the α-Carbon Side-Chain Length in the Mechanism of Action, Cytotoxicity, and Behavioral Effects in Mice

Abstract: Synthetic cathinones are β-keto amphetamine derivatives whose appearance has increased dramatically in the past decades. N-Ethyl substituted cathinones have been proven to potently inhibit dopamine (DA) uptake and induce psychostimulant and rewarding effects in mice. However, little is known about the influence of the alpha-carbon side-chain length of N-ethyl cathinones on their pharmacological and toxicological effects. Thus, the aim of this study was to synthesize and investigate the in vitro and in vivo eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 61 publications
0
2
0
Order By: Relevance
“…Research on N-ethyl-hexedrone analogues has demonstrated that the potency of DA uptake inhibitors increases as the aliphatic side chain extends from methyl to propyl. However, as the chain length increases from butyl to pentyl, the potency decreases [74]. On the other hand, longer α-carbon side chains of SCs resulted in increased cytotoxic properties in PC12 cells, probably due to their enhanced membrane penetration [74].…”
Section: Neurotransmittersmentioning
confidence: 99%
See 1 more Smart Citation
“…Research on N-ethyl-hexedrone analogues has demonstrated that the potency of DA uptake inhibitors increases as the aliphatic side chain extends from methyl to propyl. However, as the chain length increases from butyl to pentyl, the potency decreases [74]. On the other hand, longer α-carbon side chains of SCs resulted in increased cytotoxic properties in PC12 cells, probably due to their enhanced membrane penetration [74].…”
Section: Neurotransmittersmentioning
confidence: 99%
“…However, as the chain length increases from butyl to pentyl, the potency decreases [74]. On the other hand, longer α-carbon side chains of SCs resulted in increased cytotoxic properties in PC12 cells, probably due to their enhanced membrane penetration [74].…”
Section: Neurotransmittersmentioning
confidence: 99%
“…53 Moreover, our group recently showed a correlation of the binding efficacy at DAT with an increase in locomotion at an intermediate dose (10 mg/kg) of N-etlyl-pentedrone (NEPD) analogs. 54 Reward. DA is the primary neurotransmitter associated with reward and pleasure.…”
Section: ■ Mechanism Of Actionmentioning
confidence: 99%
“…142 Nonetheless, amphetamine-cathinone analogues toxicity studies should be performed in order to confirm this increased toxicity of amphetamines over cathinones is maintained for other substituents, as other studies seem to indicate that cathinones could induce seizures at lower doses than amphetamine or even -with the addition of certain substitutions in their chemical scaffold -cause more cytotoxic effects than methamphetamine. 54,133 Synthetic cathinones can suffer modifications in the aromatic ring (i), in the length of the aliphatic side chain (ii) and in the terminal amino group (iii). Therefore, SARs aim to identify what role do these modifications in the chemical scaffold of the cathinone play in their neuropharmacological and toxicological effects.…”
Section: ■ Structure−activity Relationship Of Synthetic Cathinonesmentioning
confidence: 99%
See 1 more Smart Citation